2021
DOI: 10.3390/ijerph18115577
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Self-Esteem, Psychological Stress, and the Risk of Exercise Dependence

Abstract: Body concerns and stress-related disorders are increasing in the younger population in a wide range of nations. Studies find links between both self-worth, exercise dependence, and self-esteem in relation to stress, but few have considered all three variables in relation to one another. The present study explored whether the co-appearance of high levels of psychological distress, and low levels of self-esteem may be a vulnerability factor for developing exercise dependence by studying the links between self-es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 84 publications
0
9
0
Order By: Relevance
“…While there is evidence to suggest that a diagnosed food allergy increases the likelihood of developing a subsequent eating disorder (Jafri et al, 2021 ), it is also possible that the fear and anxiety regarding food and eating in a pre-existing eating disorder may lead to self-diagnosis to gain social acceptance for food exclusion. Likewise, the association in the present study between exercise addiction and food intolerances can potentially be explained by increased attention to the body and its reactions in athletes at risk of exercise addiction, since exercise addiction may develop as a way of dealing with difficult emotions and low self-esteem where one tries to get better mentally by finding simple physical explanations (Wågan et al, 2021 ). Therefore, some athletes, specifically those with secondary exercise addiction, may use food elimination as a part of their coping strategy.…”
Section: Discussionmentioning
confidence: 65%
“…While there is evidence to suggest that a diagnosed food allergy increases the likelihood of developing a subsequent eating disorder (Jafri et al, 2021 ), it is also possible that the fear and anxiety regarding food and eating in a pre-existing eating disorder may lead to self-diagnosis to gain social acceptance for food exclusion. Likewise, the association in the present study between exercise addiction and food intolerances can potentially be explained by increased attention to the body and its reactions in athletes at risk of exercise addiction, since exercise addiction may develop as a way of dealing with difficult emotions and low self-esteem where one tries to get better mentally by finding simple physical explanations (Wågan et al, 2021 ). Therefore, some athletes, specifically those with secondary exercise addiction, may use food elimination as a part of their coping strategy.…”
Section: Discussionmentioning
confidence: 65%
“…Interestingly, our findings show that the emotional element of exercise has the most aversive effects on individuals' self-esteem, body image, and body satisfaction, and not compulsive exercise scores as a whole. Next to cross-sectional studies (e.g., [37]), future research should involve experimental studies where measures are manipulated to investigate the causal direction of the effect [36]. For example, a study that manipulates participants' levels of self-esteem and compares scores on the OEQ scale between conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Golshani et al found that mental toughness could moderate the association between heavy exercising and greater mental health issues in that lower mental toughness was associated with worse mental health issues among heavy exercisers [32]. Interestingly, mental toughness was negatively associated with neuroticism in ultraendurance athletes [56], Moreover, neuroticism could heighten negative affect and explain the maintenance of unhealthy behavior, which is supported by the association and moderate positive correlation between neuroticism and the withdrawal effect [90,95,96].…”
Section: Discussionmentioning
confidence: 88%